Comparing the short‐term outcomes of laparoscopic distal gastrectomy with D1+ and D2 lymph node dissection for gastric cancer. Issue 2 (25th January 2016) - Goto, Hironobu; Yasuda, Takashi; Oshikiri, Taro; Kanaji, Shingo; Kawasaki, Kentaro; Imanishi, Tatsuya; Oyama, Masato; Kakinoki, Keitaro; Ohara, Tadayuki; Sendo, Hiroyoshi; Fujino, Yasuhiro; Tominaga, Masahiro; et al.
Abstract: Introduction: Laparoscopic distal gastrectomy (LDG) with D1+ lymph node dissection (LND) for early gastric cancer has been widely accepted. However, LDG with D2 LND for advanced gastric cancer remains in limited use. The aim of this retrospective study was to clarify the safety of LDG with D2 LND for gastric cancer. Methods: From January 2010 to September 2014, 296 patients underwent LDG; those who received D1+ LND ( n = 230) or D2 LND ( n = 66) were included in this study. The clinicopathological characteristics and short‐term outcomes of both groups were investigated and compared. Results: There were no significant differences in the incidence of postoperative complications between the two groups. However, the frequency of infectious intra‐abdominal complications was higher in the D2 LND group than in the D1+ LND group. Additionally, a lower risk of infectious intra‐abdominal complications was seen with certified than with uncertified operators. Conclusion: The evaluation of short‐term outcomes demonstrated that LDG with D2 LND is generally feasible. However, the risk of infectious intra‐abdominal complications is higher with D2 LND than with D1+ LND. Also, D2 LND should be performed by trained operators.